The exponential dielectric relaxation dynamics in a secondary alcohol's supercooled liquid and glassy states - VIJ, JAGDISH KUMAR (My University, 2000)
To gain insight into a recent observation that the prominent, Debye-type relaxation process observed for a primary alcohol may not be the a-relaxation process associated with molecular diffusion of a liquid @Europhys. Lett. 40, 549 ~1997!, J. Chem. Phys. 107, 1086 ~1997!#, the dielectric spectra of an uncrystallizable secondary alcohol, 5-methyl-2-hexanol, has been investigated by broadband spectroscopy. Measurements made over a temperature range from 110 to 298 K showed that three relaxation processes occur. Processes I and II have a non-Arrhenius variation of the relaxation rate with temperature, and process III an Arrhenius. Only process I, the slowest of the three, has a single relaxation rate, the other two, a broad distribution. The contribution to permittivity from process II was 0.8, i.e., ;3% of the static permittivity, and from process III, the fastest was 0.1, i.e., ;0.3%. It is argued that the mechanism of process I is the breaking followed by dipolar reorientation and reforming of the H-bonds in the intermolecularly H-bonded structure, and process II is that of the orientation of the other dipolar groups, such as the -OR group. Process III is the usual Johari? Goldstein process. For 5-methyl-2-hexanol, the mode-coupling and another theory by Souletie and Bertrand @J. Phys. I 1, 1627 ~1991!# seem to agree with the relaxation rate of processes I and II, and predict temperatures for 1024 Hz relaxation rate, within a few degrees of that expected.
PUBLISHED
Keywords: Condensed matter physics; dielectric relaxation